2008
DOI: 10.1080/08870440701619957
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms, impairment and illness intrusiveness–their relationship with depression in women with CFS/ME

Abstract: Chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) is an illness in which physiological and psychological factors are believed to interact to cause and maintain CFS/ME in an individual predisposed to it. The various symptoms and impairments associated with CFS/ME have a large impact on quality of life. The purpose of the present study was to identify the extent to which the core symptoms and impairments associated with CFS/ME relate to depression in women with CFS/ME, and to discover whether these rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 46 publications
1
37
0
Order By: Relevance
“…The only illnesses more intrusive were fibromyalgia, HIV, anxiety disorders, and CFS/ME, the latter being an illness, which is acknowledged to be highly intrusive indeed, because of the impact of the illness in virtually every aspect of life (23,35). The symptoms of CFS/ME also are unpredictable, which may contribute to its intrusiveness (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only illnesses more intrusive were fibromyalgia, HIV, anxiety disorders, and CFS/ME, the latter being an illness, which is acknowledged to be highly intrusive indeed, because of the impact of the illness in virtually every aspect of life (23,35). The symptoms of CFS/ME also are unpredictable, which may contribute to its intrusiveness (36).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that illness intrusiveness relates positively to depression (21,22) and that different illnesses vary in the levels of intrusiveness into the various life domains that are affected; they also may differ in how depressing the intrusion is. For instance, chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) was most depressing in the area of the relationship with partner, self-expression, and diet (23), although the relationship with partner was not the most intrusive domain. The intrusiveness of an illness means that people with chronic illness often give up previously valued activities or hobbies; their world narrows.…”
mentioning
confidence: 99%
“…On measures assessing the impact of disorders on daily life, patients with ME/CFS record higher scores than patients with various types of cancer, rheumatoid arthritis, multiple sclerosis, endstage renal disease, depression and bipolar disorder [2][3][4]. One of the cardinal features of ME/CFS is the exacerbation of fatigue and other symptoms following minimal exertion [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…Variation also exists in terms of whether ME/CFS has been self-reported or clinically assessed; a recent meta-analysis calculated pooled prevalence rates of 3.28% and 0.76%, respectively 9. However, what is apparent is that this condition, whether self-identified or diagnosed objectively, is highly intrusive into individuals’ lives, often disrupting work, interpersonal relationships, and previously enjoyed recreational activities 10. In addition, ME/CFS has a substantial impact on the wider economy; the average cost in treatments, lost income, and benefit payments was found to be £3,515 per individual with ME/CFS over a 3-month period 11.…”
mentioning
confidence: 99%